Liza : born a star - Leigh, Wendy; Karten, Stephen (New York, N.Y., U.S.A. : Dutton, 1993)
A biography of Liza Minnelli, the daughter of Judy Garland and Vincent Minnelli. A story of triumph and tragedy but unlike Judy, Liza has endured
Keywords: Minnelli, Liza; Singers -- United States -- Biography